Developing of Multiple Intelligences in students with the Two Stay Two Strays Type - Hasnidar Hasnidar; Sulihin Sulihin; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2020)
The research objective is as a universal effort to provide variety relevant contributions to society as well as to identify new challenges must be faced, or referred to as multiple intelligences so that students can actualize multiple intelligences or multiple intelligences including emotions and spirituality. The Two Stay Two Stray (TSTS) Model of Cooperative Learning is a solution to student problems in cooperative learning which also adds to the elements of social interaction in learning. In cooperative learning, students learn together in small groups helping one another. Classes are arranged in groups of 4 or 5 students, with heterogeneous abilities. The results showed that there was an interaction between the learning process experienced by students and the teaching process by educators or teachers. Students can change their lives to be of better quality both physically, mentally, emotionally and spiritually and later it can be said to be successful in the educational process, namely achieving changes in behavior in students. It is clear that we cannot rely on intellectual alone, that IQ only contributes about 20% of the factors that determine a success, the remaining 80% comes from other factors including Emotional Intelligence in the multiple intelligence categories”. As human learner students who can be said to be successful in education and to achieve educational goals, namely education as a whole human being, here students are required to actualize all three intelligences at once, namely intellectual, emotional and spiritual. For improvement in the learning process both for educators and for students in particular, it is hoped that this research will be able to make a useful contribution to the development of science, especially in learning and character building by having properties such as integrity, humility, tolerance, restraint. , loyalty, justice, patience, simplicity, and through the teaching and learning process.